OPTIMIZATION OF COMPOSITIONS OF BENTONITIC COMPOUNDS FOR UNIFIED SAND BLENDS - D. M. Kukuj; I. B. Odarchenko; Ju. I. Lednev (Литьë и металлургия)
It is shown that the main task of experimental investigations of the chemically modified compounds was determination of influence of their components on exploitation characteristics of binding agent.